Acute and delayed effects of Ramadan intermittent fasting on the postural control of elite judokas: focus on mobility and dynamic balance performance - Souissi, N.; Zouita, A.; Abedelmalek, S.; Ammar, A.; Ezzedine, G.; Trabelsi, K.; Dziri, K.; Clark, C.; Souissi, N.; Chamari, K. (Sport Sciences for Health, 2025)
Background Ramadan intermittent fasting (RIF) induces significant physiologic changes, including alterations in sleep patterns, energy intake, and hydration status, which may affect athletic performance. Given the importance of postural control in judo, understanding the impact of RIF on mobility and dynamic balance is crucial for optimizing performance and injury prevention.